Student Expectations and Reflections of a Study Away Course Experience to Washington, D.C. - Courtney Meyers; Shannon Arnold (Journal of Applied Communications, 2016)
Active, out-of-the-class learning experiences have proven to provide students with a variety of benefits. One way to offer these valuable experiential education opportunities this is through study away to international or domestic destinations. The purpose of this study was to explore students’ perceptions of a study away course experience to Washington, D.C. This course was a collaborative effort between two universities. Twenty-two students participated in the study away experience and 21 completed pre- and post-trip questionnaires to determine their expectations and reflections of the experience. Through qualitative analysis of students’ open-ended responses, emergent themes were identified. Students expected to gain a new experience, network with others, and have an enjoyable trip. Post-trip reflections revealed students gained a great deal more than they anticipated, both personally and academically. Recommendations for practice and research are provided.
Keywords: Content Analysis; Expectations; Experiential Learning; Qualitative; Study Away; Reflection; Washington; D.C.